Using Neurospora to demonstrate the unidirectional nature of fungal mating. - Kevin McCluskey (Fungal Genetics Reports, 2005)
Different fungi have been used to demonstrate mating in fungi including Neurospora (Griffiths, 1979), Aspergillus (Denison, 2000), and Sordaria (Fields, 1970) and kits for demonstrating mating in Sordaria are available from Carolina Biological, Inc. The present demonstration allows students to see both that fungi have different mating types and that one strain acts as the female parent. It takes advantage of the rapidity of Neurospora growth and the ease of using fluffy strains (Table 1). Strains carrying the fluffy lesion are mated with fl per-1 strains and the pattern of perethecial color on the resulting plates shows which strain was the female parent.